TRIM proteins: A 'swiss army knife' of antiviral immunity. - Elise Chabot; David Durantel; Julie Lucifora (PLoS Pathogens)
With their modular structure and E3 ubiquitin ligase activity, Tripartite motif (TRIM) proteins interact with a wide range of cellular and viral substrates. This review summarizes how they have emerged as key players in the antiviral response. Shortly, TRIM proteins were shown (i) to enhance pro-inflammatory cytokines production by interacting with pattern recognition receptors and downstream components of immune signaling pathways, (ii) to interfere with viral trafficking by interacting with the cytoskeleton, and (iii) to exhibit direct antiviral effects by targeting viral proteins for proteasomal degradation or inducing autophagy. This combination of actions underscores TRIMs as a potent innate defense system, but also makes them vulnerable to viral evasion strategies.